Computation offloading in smart mobile devices and comparison study on frameworks - Piramu Preethika, SK; R. Gobinath, Dr (International Journal of Engineering and Technology, 2018)
Technology in the hands of young professionals leads to many superficial inventions among that smart mobile device are now with all hu-man beings who may be in the village or in a modern town always busy looking at their mobile devices. People interacting with social media or many online games through smart mobile device leads the battery power down and slower the performance. Mobile Cloud Computation offloading is the best strategy to overcome this pitfall. Binding of Mobile devices to the powerful cloud with the side support from tele-communication is called Mobile cloud computing. Offloading takes the heavier computation to the cloud through the network and resolves the problem there and come back to smart mobile device. This paper compares and contrasts the features of offloading types and frame-works.Â Â Â